Model Penerimaan Teknologi (TAM) dalam Adopsi Pembayaran Digital: Kajian Sistematik dan Sintesis Konseptual - Andas, Meidina Aqsari; Yulita, Tiffani; Lisna, Yenita; Irwansyah, Irwansyah (Syntax Literate, 2025)
The transformation of the financial system to digital payments has encouraged changes in the transaction patterns of Indonesian people, but the acceptance rate among informal MSMEs is still low. This study aims to analyze the factors influencing the adoption of digital payments using the Technology Acceptance Model (TAM) framework. The method used is Systematic Literature Review (SLR) which follows the PRISMA 2020 guidelines, with article searches on the Scopus and Semantic Scholar databases for the period 2013–2025. Of the 200 articles identified, 30 articles met the inclusion criteria after going through the identification, screening, eligibility, and inclusion stages. The results of the synthesis showed that the two main constructs of TAM, namely Perceived Usefulness (PU) and Perceived Ease of Use (PEOU), were the most dominant predictors of adoption intention (90% of studies). The most influential external variables are Perceived Security, Trust, and Social Influence, which are consistently additional determinants in the context of digital payments. These findings confirm that the acceptance of digital payments is influenced by perceptions of value, convenience, trust, and social support. Theoretically, this study strengthens and expands the TAM model by including the trust and social dimensions. Further research is recommended to empirically test this synthesis model in informal MSMEs in Indonesia.